ITP-QoL Questionnaire for Children with Immune Thrombocytopenia: Italian Version validation's. (1st September 2014) - Giordano, Paola; Lassandro, Giuseppe; Giona, Fiorina; Jankovic, Momcilo; Nardi, Margherita; Nobili, Bruno; Notarangelo, Lucia Dora; Russo, Giovanna; Mackensen, Sylvia von
<x xml:space="preserve">Abstract</x> Background: The ITP-QoL is a disease-specific questionnaire for the assessment of health-related quality of life (HRQoL) in children with immune thrombocytopenia (ITP) and their parents. The aim of this study was to test the psychometric characteristics of the ITP-QoL in the Italian pediatric population in terms of validity and reliability. Procedure: Children aged 8–16 years with acute or chronic ITP and their parents were recruited in Italy. Participants completed the ITP-QoL together with other patient-reported outcomes (PROs). Reliability was calculated using Cronbach's alpha. Convergent validity was determined by means of the Pearson correlation coefficients. Results: A total of 91 ITP patients, mean age of 12.11 ± 2.47 years, and their parents participated; 61.5% of the patients were female. Two patients had acute ITP and 30.2% had a moderate to severe status of ITP. Cutaneous symptoms were more frequent than mucosal symptoms. Due to item and scale analyses 20 items were deleted from the original ITP-QoL. Internal consistency of the ITP-QoL was found to be good with Cronbach's alpha exceeding α = 0.70 for all but one subscale. Concerning convergent validity "moderate" to "high" negative correlations were found between ITP-QoL and KINDL subscales. The ITP-QoL was able to discriminate between clinical subgroups such as number of days lost at school due to ITP and hospitalization. Conclusions: Our study was able to demonstrate that the Italian version of ITP-QoL (for children aged 8–16 years) is a valid and reliable instrument for the assessment of HRQoL in children with ITP.